Increasing Fracture Risk Associates With Plasma Circulating MicroRNAs in Aging People’s Sarcopenia - He, Nana; Zhang, Yuelin; Zhang, Yue; Feng, Beili; Zheng, Zaixing; Wang, Dongjuan; Zhang, Shun; Ye, Honghua (Frontiers in Physiology, 2021)
Aging is accompanied by progressive declines in muscle mass and strength, and in bone mineral density (BMD). Sarcopenia is closely associated with osteoporosis in the elderly, which can lead to abnormal gait, balance disorders, and dysfunctions, and increase the risk of falls, fractures, weakness, and death. MicroRNAs (miRNAs, miRs) are short, non-coding RNA molecules that fine-tune posttranscriptional protein expression, little is known about their participation in age-associated osteoporosis and sarcopenia. The present study is aimed to identify those microRNAs (miRNAs, miRs) as possible biomarkers of age-associated sarcopenia that correlated with a fracture in human blood. In our study, ten fracture risk-related miRNAs (miR-21-5p, miR-23a-3p, miR-24-3p, miR-93-5p, miR-100-5p, miR-122-5p, miR-124-3p, miR-125b-5p, miR-148a-3p, and miR-637) were analyzed. For the initial screening, we determined the abundance of fracture risk-associated miR-21-5p, miR-23a-3p, miR-24-3p, miR-93-5p, miR-100-5p, miR-122-5p, miR-124-3p, miR-125b-5p, miR-148a-3p, and miR-637 by real-time RT-PCR most frequently detected in enrolled 93 elderly with sarcopenia and non-sarcopenia, respectively. Statistically, the relative expression levels of plasma miR-23a-3p, miR-93-5p, and miR-637 were significantly decreased in the sarcopenia group compared to the non-sarcopenia group, while the levels of other miRNAs did not change significantly. Moreover, we showed that the levels of ASM/Height2, handgrip strength, and 4-meter velocity in the sarcopenia group were significantly lower than those in the non-sarcopenia group. We expanded the sample size to further detection and analysis and found that plasma miR-23a-3p, miR-93-5p, and miR-637 levels in the sarcopenia group were significantly decreased compared to the non-sarcopenia group, which is consistent with the results of the initial screening experiment. From our analysis, plasma miR-93-5p and miR-637 level changes were significantly correlated with ASM/Height2. Furthermore, miR-23a and miR-93-5p changes were significantly correlated with ASM/Height2 in females, while no significant correlations were found between miRNAs changes and these diagnostic indexes in males after adjusting sex. The study showed that plasma miRNAs changed in an aging-related sarcopenia manner and were associated with increased fracture risk. In aging patients, plasma miR-23a-3p, miR-93-5p, and miR-637have potential as biomarkers of sarcopenia, which can affect the development of physiological dysfunction and may be also used in the fracture risk assessment of these patients.